Exposure to intrauterine diabetes and post-natal high-fat diet: Effects on the endocrine pancreas of adult rat female pups - Barco, Vinícius S. [UNESP] (2022)
Aims: To evaluate the morphological changes in the pancreatic islet cells of adult female pups born to diabetic rats and fed a high-fat diet. Main methods: Female Sprague-Dawley rats were distributed into four experimental groups (n = 10 animals/group): 1) female pups from non-diabetic dams and fed a standard diet (OC/SD), 2) female pups from non-diabetic dams and fed a high-fat (OC/HFD), 3) female pups from diabetic dams and fed a standard diet (OD/SD) and 4) female pups from diabetic dams and fed a high-fat diet (OD/HFD). In adulthood, the rats were submitted to the oral glucose tolerance test and later euthanized to collect the pancreas for the analysis of pancreatic islets. Key findings: The OC/HFD and OD/SD groups showed an increased percentage of cells immunostained for insulin and a decreased percentage and intensity of staining for somatostatin. The OD/HFD group showed an increased percentage of cells immunostained for insulin and glucagon and a higher staining intensity for glucagon. There was a progressive increase in blood glucose in the OC/HFD, OD/SD, and OD/HFD groups. Significance: The association between maternal diabetes and/or the administration of high-fat diet-induced changes in the pancreatic hormonal triad of female pups in adulthood. In turn, these changes in the pancreatic islets are not capable of causing decreased blood glucose in the offspring, contributing to the development of glucose intolerance in adulthood.